Critical Reading Skills of the Descriptive Genre Through E-Learning - Gusnetti, Gusnetti; Morelent, Yetty; Nita, Olin (KnE Social Sciences, 2022)
It has been found that in reading lectures, students at Bung Hatta University had difficulty understanding the text because they did not know about the genre of the text. This is because students study theory more than they practice reading. The purpose of this research was to describe the critical reading ability of Indonesian Language Education (Pindo) FKIP students at Bung Hatta University by applying the descriptive text genre. Theories proposed by Akaaya, Haromi and Akin were employed. Qualitative and quantitative methods were used. The research subjects were 23 students of the Indonesian Language and Literature Education Study Program, FKIP Bung Hatta University, Padang, class of 2020/2021. The score obtained for making and answering questions was 8.65, determining the structure of descriptive texts was 8.52, determining the structure of exposition texts was 8.60, concluding news texts was 7.78, and commenting on news texts was 7.91. The results showed that overall, the students of Pindo FKIP Bung Hatta University were able to read critically with a score of 8.25, which can be categorized as good. Keywords: descriptive text genre, critical reading, e-learning